Comparative study between polymeric superplasticizers - Aguiar, J. L. Barroso de (2008)
The present work aims to compare the properties of concrete produced with different incorporation of superplasticizers. Superplasticizers or water reducing agents are considered the most important chemical admixtures in concrete mixtures, due to their influence on the properties of both fresh and hardened concrete. Superplasticizers are usually polymer based products. Three superplasticizers were tested: two sulphonated naphthalene based and one polycarboxylate based polymer. The performance of the concretes was assessed according to the water reduction, compressive strength and air content. The results show that superplasticizers contributed significantly to the increase in compressive strength while maintain workability of the concrete mixes. The advantage of polycarboxylate was that the amount used to obtain similar compressive strengths was about four times lower.